Reliable and generic liquid chromatography/mass spectrometry quantification of short peptides using a stable‐isotope‐labeled labeling agent. (6th October 2020) - Kleinnijenhuis, Anne J.; Vergauwen, Bjorn; van Holthoon, Frédérique L.; Hekman, Maarten
Abstract : Rationale: It is important to investigate the behavior of protein hydrolysate components in both in vitro and in vivo studies, to support the elucidation of their biological functions. As protein hydrolysates and biological matrices are highly complex mixtures, it is essential to apply fully reliable and flexible analytical approaches. Methods: A novel and generic Liquid Chromatography/Mass Spectrometry methodology was developed to analyze short peptides. A stable‐isotope‐labeled labeling agent 6‐aminoquinolyl‐ N ‐hydroxysuccinimidyl carbamate ( 13 C3 ) was synthesized and used to prepare internal standards from non‐labeled analyte peptides. The amino acid and peptides p, p G, Pp, GPp and Pp G (where p stands for hydroxyproline) were used for proof of principle. Results: The method showed acceptable performance in solvent, in simulated gastrointestinal fluid and in serum. The (linear) dynamic range expanded to over four orders of magnitude, which is very useful when multiple analytes are analyzed in a biological matrix, due to the large differences in concentrations observed for endogenous and protein hydrolysate components. The method provides absolute‐quantitative results and is fully accountable on the single‐sample and single‐component level. Conclusions: The methodology can be applied to reliably quantify protein hydrolysate nutraceutical components at various stages during their in vivo processing. Internal standards can also be synthesized for other short peptides whenever they are expected to have biological relevance and require quantification. Overall this provides an excellent analytical tool to support the elucidation of the biological functions of protein hydrolysate components.